Phosphate Functionalized Graphene with Tunable Mechanical Properties. (1st October 2013) - Goods, John B.; Sydlik, Stefanie A.; Walish, Joseph J.; Swager, Timothy M.
<x xml:space="preserve">Abstract</x> The synthesis of a covalently modified graphene oxide derivative with exceptional and tunable compressive strength is reported. Treatment of graphene oxide with triethyl phosphite in the presence of LiBr produces monolithic structures comprised of lithium phosphate oligomers tethered to graphene through covalent phosphonate linkages. Variation of the both phosphate content and associated cation produces materials of various compressive strengths and elasticity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>